Association between the Risk of Preterm Birth and Low Birth Weight with Periodontal Disease in Pregnant Women: An Umbrella Review - Padilla-Cáceres, Tania (2023)
Background: The purpose of this review is to determine the association between the risk of preterm birth and low birth weight in newborns and periodontal disease in pregnant women. Methods: A bibliographic search was carried out until November 2021 in the following biomedical databases: PubMed/Medline, Cochrane Library, Scopus, EMBASE, Web of Science, Scielo, LILACS and Google Scholar. Studies reporting the association between the risk of preterm birth and low birth weight in newborns with periodontal disease in pregnant women, which were systematic reviews, in English and without time limits were included. AMSTAR-2 was used to assess the risk of the included studies, and the GRADEPro GDT tool was used to assess the quality of the evidence and the strength of the recommendation of the results. Results: The preliminary search yielded a total of 161 articles, discarding those that did not meet the selection criteria, leaving only 15 articles. Seven articles were entered into a meta-analysis, and it was found that there is an association between the risk of preterm birth and low birth weight in newborns with periodontal disease in pregnant women. Conclusions: There is an association between the risk of preterm birth and low birth weight in newborns with periodontal disease in pregnant women.